AN ANALYSIS OF CODE MIXING ON THE INDAH G SHOW’S YOUTUBE PODCAST - Dharmadiah, Dharmadiah; Tarihoran, Rezky Khoirina (Fakultas Sastra UMN AL Washliyah, 2025)
Code mixing is changing one language to another during a conversation or in written or spoken text. The data used in this study is The Indah G Show's Youtube Podcast entitled Chindo Jakarta vs Chindo Surabaya. This study aims to determine the form of code mixing contained in The Indah G Show's Youtube Podcast. The method used is a qualitative method. The results of this study indicate that there are 3 types of code mixing based on the Musyken’s theory, namely Inserstion, Alternation, and Lexicalization Congruent. The researcher found 29 data, including insertion 9 data, alternation 18 data, and lexicalization congruent 2 data. Based on these results, the researcher concluded that alternation is the type of code mixing that appears most often.